The Influence of Nutritional Coaching (in the Network) on the Level of Nutritional Knowledge of Mothers of Stunting Toddler - Alfi Rahmatillah Nur Fithriah; Sumardyono; Anik Lestari (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is still an unresolved nutritional problem. Stunting in children is the result of chronic malnutrition or impaired growth and development in the past. The stunting rate among toddlers in Mojokerto Regency is 27.4% (2021). This research aims to analyze the influence of nutritional coaching (in the network) on the level of nutritional knowledge of mothers of stunting toddlers in Sooko District, Mojokerto Regency. This research is a quasi-experimental research with a pretest - posttest control group design. The sampling technique used was purposive sampling. The research instrument used a nutritional knowledge questionnaire and a 24-hour recall form. The type of data is primary data with statistical analysis using Paired sample T-test. Online nutritional coaching can increase the difference in the value of the mother's nutritional knowledge level, showing significant changes between before and after treatment with a p value of 0.000. Based on statistical tests between groups, a p-value of 0.005 was obtained. Statistical tests on these differences resulted in p < 0.05, meaning the differences were significant between groups. The conclusion of this research is that online nutritional coaching via leaflets can increase the nutritional knowledge of stunted mothers of toddlers.